2003
DOI: 10.1016/s0140-1971(03)00036-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Balloon Analogue Risk Task (BART) as a predictor of adolescent real‐world risk‐taking behaviours

Abstract: The Balloon Analogue Risk Task (BART) was administered to a sample of 26 high school‐aged adolescents to test the utility of the BART as a behavioural measure of risk‐taking propensity. Data indicate that riskyness on the BART was related to self‐reported engagement in real‐world risk‐taking behaviours. These data replicate and uniquely extend past research to an adolescent sample, suggesting that the BART may be a useful addition to self‐report batteries for the assessment of risk‐taking behaviours in adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
389
3
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(416 citation statements)
references
References 8 publications
17
389
3
7
Order By: Relevance
“…Behavioral measures, and not self-reports, were significantly related to treatment outcome, consistent with earlier reports suggesting that behavioral and self-report assessments of impulsivity assessments may represent different levels of analyses, from detailing specific behavioral processes to more general trait-like impulsive tendencies (Lejuez et al, 2003, Reynolds et al, 2006. However, given the small sample size, the differences between selfreport and behavioral measures in predicting treatment outcome should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 83%
“…Behavioral measures, and not self-reports, were significantly related to treatment outcome, consistent with earlier reports suggesting that behavioral and self-report assessments of impulsivity assessments may represent different levels of analyses, from detailing specific behavioral processes to more general trait-like impulsive tendencies (Lejuez et al, 2003, Reynolds et al, 2006. However, given the small sample size, the differences between selfreport and behavioral measures in predicting treatment outcome should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 83%
“…16,34 Specifically, risk-taking on the BART is highly correlated with measures of sensation seeking, impulsivity, and deficiencies in behavioral constraint, as well as with self-reported occurrence of addiction and other risky behaviors. [16][17][18]34 The BART simulates a balloon being inflated by the participant with each click of a mouse. Each pump is worth 5 cents.…”
Section: Methodsmentioning
confidence: 99%
“…163 Paradigms measuring behaviours under specified circumstances may overcome the limitations of self-report questionnaires and prove to be valid measures of intermediate phenotypes. [164][165][166][167][168] For example, it has been demonstrated that 5-HTTLPR s allele carriers have more attentional bias towards anxiety-related stimuli compared to ll homozygotes in the dot-probe task. 168 A complementary approach will be the identification of biological endophenotypes.…”
Section: Genetic Control Of the Environmentmentioning
confidence: 99%